Effect of maturity timing on the physical performance of male Polish basketball players aged 13 to 15 years - Gryko, K. (Scientific Reports, 2021)
The aims of this study were (i) to identify the motor potential and basic anthropometric characteristics of Polish basketball players aged 13 to 15 years, (ii) to demonstrate the effect of maturity timing on the results achieved in motor tests and basic body composition parameters, and (iii) to determine which index contributes most to the prediction of performance in the individual tests of speed, jumping ability, agility, and endurance. The sample included 818 male Polish players. Analysis of values related to age-adjusted characteristics showed that in the under 13-year-old group, early maturers had significantly better results (except for stage 1 in the agility test) than average maturers. However, in the endurance test in the under 14- and 15-year-old groups (both distance covered and VO2max), the average maturers obtained higher values. Furthermore, maturity differentiation in the under 14- and 15-year-old groups significantly affected body size, 20-m sprinting time (under 14-year-old group only), and the results of all jumping tests. ANCOVA results (age, body height, and body mass as covariates) showed better results of early maturers in the under 13-year-old group. The opposite trend was observed in the under 14- to 15-year-old groups, where early maturing individuals performed worse in the running vertical jump (VJ) and endurance tests (both distances covered and VO2max). Maturity timing (VJ and VO2max), chronological age (5 m, 10 m, 20 m, agility, and VO2max tests), body height (all tests), body mass (5 m), and the interaction between body mass and height (10 m, 20 m, agility, standing vertical jump, vertical jump) were significant (adjusted R2 = 0.08-0.25; p < 0.001) predictors of motor skills. These findings can be helpful in quantifying and controlling the results of youth sports programs adjusted to biological requirements used in the training process.